Alleviation of alloxan-induced diabetes and its complications in rats by Actinodaphne hookeri leaf extract - Dharmeshkumar D. Prajapati; N. M. Patel; R. V. Savadi; K. S. Akki; K. Mruthunjaya (Bangladesh Pharmacological Society, 2008)
Leaves of Actinodaphne hookeri Meissn (Family Lauraceae; local name: Pisa) has been in use traditionally for the treatment of diabetes and disorders of the urinary tract which are more common in Chattisgarh and eastern part of India. In the present study, leaves of A. hookeri were subjected to phytochemical investigation and evaluated for anti-diabetic activity. The ethanol and the chloroform extract were found to have significant (p<0.01) blood glucose lowering effect. The extracts also significantly (p<0.01) lowered the increased serum cholesterol and low density lipoprotein levels. Preliminary phytochemical investigation revealed the presence of alkaloids, flavonoids, triterpenoids and glycosides as the major constituents in the ethanol extract. The chloroform extract also showed significant (p<0.01) antihyperglycemic activity and contained alkaloids and triterpenes. It is concluded that the antidiabetic activity of A. hookeri may be due to the presence of alkaloids and triterpenes, and might be promising for the development of phytomedicine for diabetes mellitus along with its associated complications.